Characteristics of Raw-Starch Degrading Amylase Bacteria from Natar Hot Spring Lampung - Fina Khaerunnisa Frima; Rina Budi Satiyarti; Yulistia Anggraini; Erga Syafitri; Ika Agus Rini (Jurnal Kimia Sains dan Aplikasi, 2020)
Indonesia has a diversity of hot spring as a habitat of bacteria. One of the hot springs is Natar hot spring, Lampung. This study is to report the characteristics of a bacterium called Nat1 isolate that produces amylase to degrade raw starch from Natar hot spring. Water samples were taken from hot springs with a temperature of 45°C and a pH of 7.0. Nat1 was isolated by screening on the medium of Starch-Luria Bertani at 37°C. Its amylase-producing bacteria showed an optimum amylolytic activity of a crude enzyme of Nat1 isolate in soluble starch was 267.2774 U/mL at 60°C. Genotypic identification results using the 16S rRNA gene showed that the Nat1 isolate is identified as Panninobacter phragmatetus. A crude enzyme of Nat1 isolate showed a novel amylase ability and could degrade the raw starch substrates, such as corn and sago, with the amount of reducing sugar for each raw starch, 37.0688 µmol/mg, and 24.2697 µmol/mg. In conclusion, Nat1 amylase is potentially used in industry for its ability to degrade raw starch directly.